2020
DOI: 10.1186/s13046-020-01589-9
|View full text |Cite|
|
Sign up to set email alerts
|

SNCG promotes the progression and metastasis of high-grade serous ovarian cancer via targeting the PI3K/AKT signaling pathway

Abstract: Background The poor prognosis of patients with ovarian cancer is mainly due to cancer progression. γ-Synuclein (SNCG) has reported as a critical player in cancer metastasis. However, its biological roles and mechanism are yet incompletely understood in ovarian cancer, especially in high-grade serous ovarian cancer (HGSOC). Methods This is a retrospective study of 312 patients with ovarian cancer at a single center between 2006 and 2016. Ovarian cancer tissues were stained by immunohistochemistry to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
2
30
0
Order By: Relevance
“…The degree of staining in the TRPV1 sections was observed and scored by a pathologist. According to previously defined criteria [31,32], the percentage of TRPV1 positivity was scored from 0 to 3 as follows: 0, < 10%; 1, 10-30%; 2, 30-50%; 3, > 50%. Staining intensity was scored according to a 4-point scale as follows: 0 (no staining); 1 (weak staining, light yellow); 2 (moderate staining, yellowish brown); and 3 (strong staining, brown).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…The degree of staining in the TRPV1 sections was observed and scored by a pathologist. According to previously defined criteria [31,32], the percentage of TRPV1 positivity was scored from 0 to 3 as follows: 0, < 10%; 1, 10-30%; 2, 30-50%; 3, > 50%. Staining intensity was scored according to a 4-point scale as follows: 0 (no staining); 1 (weak staining, light yellow); 2 (moderate staining, yellowish brown); and 3 (strong staining, brown).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“… 19 Recently, SNCG was identified as a key regulator in the progression and metastasis of high-grade serous ovarian cancer, of which PI3K/Akt signaling pathway acted as the potential downstream mechanism. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Precursor lesions for HGSOC tumors include STIC, SCOUT, and TP53 signatures [ 12 ]. γ -Synuclein (SNCG) has been implicated in tumor progression and metastasis in HGSOC [ 13 ]. Cheon et al identified a 10-gene signature (AEBP1, COL11A1, COL5A1, COL6A2, LOX, POSTN, SNAI2, THBS2, TIMP3, and VCAN) that is associated with poor overall survival and metastasis in patients with HGSOC [ 14 ].…”
Section: Discussionmentioning
confidence: 99%